Tax treatment of transfer rates - a comparative analytical study between the American tax system and the Algerian tax system - - benchohra, saidi; gamane, amer (Journal of Research in Finance and Accounting, 2020)
In order not to use conversion rates as a means of tax evasion by companies, some countries have devised and promulgated laws prohibiting these practices, as is the case in the United States of America as well as Algeria. This study addresses the most important features of the tax regime for transfer rates for each of them and stands for deterrent steps to combat the phenomenon of evading through transfer rates, as it was concluded that the American tax system is more accurate, robust, focused and rigorous compared to the Algerian tax system.